High-strength flame-retardant nylon composition and preparation method thereof
By combining a self-made nitrogen-phosphorus flame retardant with tanninic acid, a combination of an expanded composite flame retardant with nylon resin, modified glass fiber and toughening agent, a high-strength flame retardant nylon composition was prepared, solving the problems of flammability and mechanical properties of nylon materials, and achieving both high strength and high flame retardant properties.
Patent Information
- Application Number
- CN202411979466.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing nylon materials are flammable, unstable flame retardant properties, and their mechanical properties are degraded after modification, and their environmental friendliness is poor.
A high-strength flame retardant nylon composition is prepared by combining a homemade nitrogen-phosphorus flame retardant with tanninic acid.
The flame retardant performance of nylon materials is significantly improved, the oxygen index is above 35%, the vertical combustion test reaches V-0, and good mechanical properties are maintained, the bending strength is above 120MPa, and the flame retardant effect is stable and environmentally friendly.
Smart Images

Figure BDA0005221189980000021 
Figure BDA0005221189980000022 
Figure BDA0005221189980000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant nylon compositions, and in particular to a high-strength flame-retardant nylon composition and a preparation method thereof. Background Art
[0002] Nylon, also known as polyamide fiber, is a general term for thermoplastic resins containing repeated amide groups (-NHCO-) on the molecular chain. It is the first synthetic fiber in the world and one of the most widely used materials in the world. However, nylon is a flammable material. Its flammability may cause safety hazards in high temperature environments or when a fire occurs. Therefore, improving the flame retardant properties of nylon materials is one of the important directions of its modification.
[0003] At present, the flame retardants used to improve the flame retardancy of nylon include inorganic flame retardants, organophosphorus flame retardants and halogen flame retardants, but there are common problems such as unstable flame retardant effect, decreased mechanical properties of nylon and poor environmental friendliness. Therefore, it is of great significance to develop a new type of intumescent flame retardant to be applied to nylon materials to further improve its flame retardancy and maintain its good mechanical properties. Summary of the invention
[0004] In view of this, the purpose of the present invention is to propose a high-strength flame-retardant nylon composition and a preparation method thereof. The flame retardant and fire resistance of nylon can be effectively improved by combining a homemade nitrogen-phosphorus flame retardant with a tannic acid flame retardant, and the prepared nylon composition has good mechanical properties, and its bending strength is higher than 120MPa.
[0005] Based on the above purpose, the present invention provides a high-strength flame-retardant nylon composition, comprising the following raw materials by weight: 100 parts of nylon resin, 5-10 parts of composite flame retardant, 10-15 parts of toughening agent, and 20-30 parts of modified glass fiber;
[0006] The composite flame retardant is prepared by mixing a homemade nitrogen-phosphorus flame retardant and tannic acid in a mass ratio of 1:(0.2-0.3);
[0007] The method for preparing the self-made nitrogen-phosphorus flame retardant comprises the following steps:
[0008] A1: Add DOPO and itaconic acid to 1,4-dioxane, stir to dissolve, reflux at 175°C for 5-7h, and cool naturally to room temperature to obtain DOPO-ITA reaction solution;
[0009] The synthetic route of DOPO-ITA is shown in Formula I:
[0010]
[0011] A2: Add pentaerythritol tetramine and EDC into DMF, stir and mix at 60°C, then dropwise add DOPO-ITA reaction solution, stir and react at 70-90°C for 3-5h, remove the solvent by rotary evaporation, and dry to obtain a self-made nitrogen-phosphorus flame retardant.
[0012] The synthesis route of the homemade nitrogen-phosphorus flame retardant is shown in Formula II:
[0013]
[0014] Furthermore, the nylon resin is one or both of nylon 6 resin and nylon 66 resin.
[0015] Furthermore, the usage ratio of DOPO, itaconic acid, 1,4-dioxane, pentaerythritol, EDC and DMF is 1 mol:1 mol:900 mL:0.25 mol:(0.01-0.02) mol:100 mL.
[0016] Furthermore, the toughening agent is one or more of ethylene-octene copolymer grafted with maleic anhydride, ethylene-vinyl acetate copolymer grafted with maleic anhydride, and ethylene-1-butene copolymer.
[0017] Furthermore, the preparation method of the modified glass fiber is: adding glass fiber into deionized water, dropping 3-isocyanatepropyltrimethoxysilane, stirring and reacting at 30-50° C. for 2-3 hours, filtering and drying to obtain the modified glass fiber.
[0018] Furthermore, the usage ratio of the glass fiber, deionized water, and 3-isocyanatepropyltrimethoxysilane is 1 g: (1.3-1.5) mL: (0.1-0.15) g.
[0019] Furthermore, the glass fiber has a diameter of 5-7 μm and a length of 2-3 mm.
[0020] The present invention also provides a method for preparing a high-strength flame-retardant nylon composition, comprising the following steps:
[0021] After the nylon resin, composite flame retardant and toughening agent are evenly mixed, they are added into a twin-screw extruder through a main feed port, and the modified glass fiber is added into the twin-screw extruder from a side feed port. After melt blending, extrusion granulation and drying, a high-strength flame-retardant nylon composition is obtained.
[0022] Furthermore, the operating temperature of each zone of the twin-screw extruder is: 230-250°C in zone 1, 240-270°C in zone 2, 245-275°C in zone 3, and 250-280°C in zone 4; the screw speed of the twin-screw extruder is 330-450rpm.
[0023] Beneficial effects of the present invention:
[0024] The nylon composition prepared by the invention has excellent flame retardant performance, an oxygen index higher than 35%, a vertical combustion test reaching V-0, and good mechanical properties, a bending strength higher than 120MPa.
[0025] The present invention uses a self-made nitrogen-phosphorus flame retardant and tannic acid to prepare an intumescent composite flame retardant, and the two synergize to further enhance the flame retardant effect. The flame retardant effect is stable and environmentally friendly. DOPO and itaconic acid are first reacted to generate DOPO-ITA, and then further reacted with pentaerythritol tetramine through amidation to generate a new nitrogen-phosphorus synergistic flame retardant. The flame retardant is a star-shaped flame retardant structure with pentaerythritol tetramine as the core and DOPO-ITA as the extended arm. When burned, it pyrolyzes to produce a large amount of nitrogen-containing non-combustible gas, H 2 O(g), etc., and absorb a lot of heat. At the same time, DOPO-ITA molecules form phosphoric acid on the surface of nylon polymers, which cooperates with tannic acid to promote the formation of a dense carbon layer on the surface of nylon polymers, blocking oxygen from entering the interior of the burning material, thereby preventing the combustion reaction from proceeding. In addition, DOPO-ITA molecules have biphenyl ring and phenanthrene ring structures, which are introduced into nylon compositions to help improve the mechanical strength of nylon compositions and improve their thermal stability. DETAILED DESCRIPTION
[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0027] The present invention provides a method for preparing a high-strength flame-retardant nylon composition according to an embodiment, comprising the following raw materials in parts by weight:
[0028] S1: Preparation of homemade nitrogen-phosphorus flame retardant:
[0029] S101: adding DOPO and itaconic acid to 1,4-dioxane, stirring to dissolve, reflux at 175° C. for 5-7 hours, and naturally cooling to room temperature to obtain a DOPO-ITA reaction solution;
[0030] The synthetic route of DOPO-ITA is shown in Formula I:
[0031]
[0032] S102: Add pentaerythritol and EDC to DMF, stir and mix at 60° C., then dropwise add DOPO-ITA reaction solution, stir and react at 70-90° C. for 3-5 h, remove the solvent by rotary evaporation, and dry to obtain a self-made nitrogen-phosphorus flame retardant;
[0033] The synthetic route of the homemade nitrogen-phosphorus flame retardant is shown in Formula II:
[0034]
[0035] The usage ratio of DOPO, itaconic acid, 1,4-dioxane, pentaerythritol, EDC and DMF is 1 mol:1 mol:900 mL:0.25 mol:(0.01-0.02) mol:100 mL;
[0036] DOPO and itaconic acid react to generate DOPO-ITA, which is then reacted with pentaerythritol tetramine through amidation to generate a new nitrogen-phosphorus synergistic flame retardant. The flame retardant is a star-shaped flame retardant structure with pentaerythritol tetramine as the core and DOPO-ITA as the extended arm. When burned, it pyrolyzes to produce a large amount of nitrogen-containing non-combustible gas, H 2 O(g), etc., and absorb a lot of heat. At the same time, DOPO-ITA molecules form phosphoric acid on the surface of nylon polymers, which promotes the formation of a dense carbon layer on the polymer surface and prevents the combustion reaction from proceeding. In addition, DOPO-ITA molecules have biphenyl ring and phenanthrene ring structures, which are introduced into nylon compositions to help improve the mechanical strength of nylon compositions and improve their thermal stability.
[0037] S2: preparing a composite flame retardant: mixing the self-made nitrogen-phosphorus flame retardant and tannic acid in a mass ratio of 1:(0.2-0.3) to obtain a composite flame retardant; the self-made nitrogen-phosphorus flame retardant and tannic acid are combined to prepare a composite flame retardant, and the two are synergistically enhanced to further enhance the flame retardant effect;
[0038] S3: preparing modified glass fiber: adding glass fiber with a diameter of 5-7 μm and a length of 2-3 mm into deionized water, dropping 3-isocyanate propyl trimethoxy silane, stirring and reacting at 30-50° C. for 2-3 hours, filtering and drying to obtain modified glass fiber; the amount ratio of the glass fiber, deionized water and 3-isocyanate propyl trimethoxy silane is 1 g: (1.3-1.5) mL: (0.1-0.15) g;
[0039] By modifying the glass fiber with 3-isocyanate propyltrimethoxysilane, the compatibility of the glass fiber in the nylon system is improved, so that the glass fiber is stably combined in the nylon system, and the strength of the nylon composition is further increased;
[0040] S4: preparing a high-strength flame-retardant nylon composition: after uniformly mixing 100 parts of nylon resin, 5-10 parts of composite flame retardant and 10-15 parts of toughening agent by mass, adding the mixture into a twin-screw extruder through a main feed port, and adding 20-30 parts of modified glass fiber into the twin-screw extruder from a side feed port, after melt blending, extrusion granulation and drying, a high-strength flame-retardant nylon composition is obtained;
[0041] The operating temperature of each zone of the twin-screw extruder is: 230-250°C for zone 1, 240-270°C for zone 2, 245-275°C for zone 3, and 250-280°C for zone 4; the screw speed of the twin-screw extruder is 330-450rpm;
[0042] Furthermore, the toughening agent is one or more of ethylene-octene copolymer grafted with maleic anhydride, ethylene-vinyl acetate copolymer grafted with maleic anhydride, and ethylene-1-butene copolymer.
[0043] Example 1
[0044] A method for preparing a high-strength flame-retardant nylon composition comprises the following raw materials in parts by weight:
[0045] S1: Preparation of homemade nitrogen-phosphorus flame retardant:
[0046] S101: adding DOPO and itaconic acid to 1,4-dioxane, stirring to dissolve, reflux at 175° C. for 5 h, and naturally cooling to room temperature to obtain a DOPO-ITA reaction solution;
[0047] S102: Add pentaerythritol tetramine and EDC to DMF, stir and mix at 60° C., then dropwise add DOPO-ITA reaction solution, stir and react at 70° C. for 3 h, remove the solvent by rotary evaporation, and dry to obtain a self-made nitrogen-phosphorus flame retardant;
[0048] The usage ratio of DOPO, itaconic acid, 1,4-dioxane, pentaerythritol, EDC and DMF is 1 mol: 1 mol: 900 mL: 0.25 mol: 0.01 mol: 100 mL;
[0049] S2: preparing a composite flame retardant: mixing the homemade nitrogen-phosphorus flame retardant and tannic acid in a mass ratio of 1:0.2 to obtain a composite flame retardant;
[0050] S3: Preparation of modified glass fiber: Add glass fiber with a diameter of 5 μm and a length of 2 mm into deionized water, add 3-isocyanate propyltrimethoxysilane dropwise, stir at 30° C. for 2 h, filter and dry to obtain modified glass fiber; the ratio of the glass fiber, deionized water and 3-isocyanate propyltrimethoxysilane is 1 g:1.3 mL:0.1 g;
[0051] S4: preparing a high-strength flame-retardant nylon composition: after uniformly mixing 100 parts of nylon 6 resin, 5 parts of composite flame retardant, and 10 parts of toughening agent ethylene-octene copolymer grafted maleic anhydride, the mixture is added into a twin-screw extruder through a main feed port, and 20 parts of modified glass fiber is added into the twin-screw extruder through a side feed port. After melt blending, extrusion granulation, and drying, a high-strength flame-retardant nylon composition is obtained;
[0052] The operating temperature of each zone of the twin-screw extruder is: 240° C. for zone 1, 260° C. for zone 2, 265° C. for zone 3, and 270° C. for zone 4; the screw speed of the twin-screw extruder is 400 rpm.
[0053] Example 2
[0054] A method for preparing a high-strength flame-retardant nylon composition comprises the following raw materials in parts by weight:
[0055] S1: Preparation of homemade nitrogen-phosphorus flame retardant:
[0056] S101: adding DOPO and itaconic acid to 1,4-dioxane, stirring to dissolve, reflux at 175° C. for 7 h, and naturally cooling to room temperature to obtain a DOPO-ITA reaction solution;
[0057] S102: Add pentaerythritol tetramine and EDC to DMF, stir and mix at 60° C., then dropwise add DOPO-ITA reaction solution, stir and react at 90° C. for 5 h, remove the solvent by rotary evaporation, and dry to obtain a self-made nitrogen-phosphorus flame retardant;
[0058] The usage ratio of DOPO, itaconic acid, 1,4-dioxane, pentaerythritol, EDC and DMF is 1 mol: 1 mol: 900 mL: 0.25 mol: 0.02 mol: 100 mL;
[0059] S2: preparing a composite flame retardant: mixing the homemade nitrogen-phosphorus flame retardant and tannic acid in a mass ratio of 1:0.3 to obtain a composite flame retardant;
[0060] S3: Preparation of modified glass fiber: Add glass fiber with a diameter of 7 μm and a length of 3 mm into deionized water, add 3-isocyanate propyltrimethoxysilane dropwise, stir at 50° C. for 3 h, filter and dry to obtain modified glass fiber; the ratio of the glass fiber, deionized water and 3-isocyanate propyltrimethoxysilane is 1 g:1.5 mL:0.15 g;
[0061] S4: preparing a high-strength flame-retardant nylon composition: after uniformly mixing 100 parts of nylon 66 resin, 10 parts of composite flame retardant, and 15 parts of toughening agent ethylene-vinyl acetate copolymer grafted maleic anhydride, the mixture is added into a twin-screw extruder through a main feed port, and 20-30 parts of modified glass fiber is added into the twin-screw extruder through a side feed port, and after melt blending, extrusion granulation, and drying, a high-strength flame-retardant nylon composition is obtained;
[0062] The operating temperature of each zone of the twin-screw extruder is: 250° C. for zone 1, 270° C. for zone 2, 275° C. for zone 3, and 280° C. for zone 4; the screw speed of the twin-screw extruder is 450 rpm.
[0063] Comparative Example 1 is the same as Example 1, except that tannic acid is used instead of the composite flame retardant in Comparative Example 1.
[0064] Comparative Example 2 is the same as Example 1, except that the composite flame retardant is replaced by a homemade nitrogen-phosphorus flame retardant in Comparative Example 2.
[0065] Comparative Example 3 is the same as Example 1, except that the composite flame retardant is prepared by uniformly mixing DOPO-ITA and tannic acid in a mass ratio of 1:0.2; and DOPO-ITA is prepared by rotary evaporating the DOPO-ITA reaction solution to remove the solvent and drying.
[0066] The nylon compositions prepared in Examples 1-2 and Comparative Examples 1-3 were injection molded to prepare flame retardant specimens, and flame retardant performance tests were performed:
[0067] The oxygen index of the nylon compositions prepared in Examples 1-2 and Comparative Examples 1-3 was measured according to GB / T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method", and the sample size was 130 mm*8 mm*4.
[0068] The nylon compositions prepared in Examples 1-2 and Comparative Examples 1-3 were vertically burned according to UL-94-2009, and the sample size was 120 mm*12 mm*3 mm.
[0069] The flame retardant performance test results are shown in Table 1:
[0070] Table 1
[0071] Group Oxygen index / % Vertical combustion Example 1 36.2 V-0 Example 2 39.4 V-0 Comparative Example 1 26.8 V-2 Comparative Example 2 31.6 V-1 Comparative Example 3 31.1 V-1
[0072] As can be seen from Table 1, the flame retardant properties of the nylon composition prepared in Examples 1-2 are significantly better than those in Comparative Examples 1-3, which proves that the flame retardant prepared by the self-made nitrogen-phosphorus flame retardant and tannic acid in the present invention can effectively improve the flame retardant and fire resistance of nylon, and the composite flame retardant system contains a large number of -OH and -COOH groups that can cross-link with -NCO in the modified glass fiber and the terminal amino group in the nylon resin, so that the nylon composition maintains good mechanical properties, and its bending strength is higher than 120MPa.
[0073] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0074] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-strength flame-retardant nylon composition, characterized in that: The invention comprises the following raw materials by weight: 100 parts of nylon resin, 5-10 parts of composite flame retardant, 10-15 parts of toughening agent and 20-30 parts of modified glass fiber; The composite flame retardant is prepared by mixing a homemade nitrogen-phosphorus flame retardant and tannic acid in a mass ratio of 1:(0.2-0.3); The method for preparing the self-made nitrogen-phosphorus flame retardant comprises the following steps: A1: Add DOPO and itaconic acid to 1,4-dioxane, stir to dissolve, reflux at 175°C for 5-7h, and cool naturally to room temperature to obtain DOPO-ITA reaction solution; A2: Add pentaerythritol tetramine and EDC into DMF, stir and mix at 60°C, then dropwise add DOPO-ITA reaction solution, stir and react at 70-90°C for 3-5h, remove the solvent by rotary evaporation, and dry to obtain a self-made nitrogen-phosphorus flame retardant.
2. A high-strength flame-retardant nylon composition according to claim 1, characterized in that: The nylon resin is one or both of nylon 6 resin and nylon 66 resin.
3. A high-strength flame-retardant nylon composition according to claim 1, characterized in that: The usage ratio of DOPO, itaconic acid, 1,4-dioxane, pentaerythritol, EDC and DMF is 1 mol:1 mol:900 mL:0.25 mol:(0.01-0.02) mol:100 mL.
4. A high-strength flame-retardant nylon composition according to claim 1, characterized in that: The toughening agent is one or more of ethylene-octene copolymer grafted with maleic anhydride, ethylene-vinyl acetate copolymer grafted with maleic anhydride, and ethylene-1-butene copolymer.
5. A high-strength flame-retardant nylon composition according to claim 1, characterized in that: The preparation method of the modified glass fiber is as follows: adding glass fiber into deionized water, dropping 3-isocyanate propyltrimethoxysilane, stirring and reacting at 30-50° C. for 2-3 hours, filtering and drying to obtain the modified glass fiber.
6. A high-strength flame-retardant nylon composition according to claim 5, characterized in that: The usage ratio of the glass fiber, deionized water and 3-isocyanatepropyltrimethoxysilane is 1 g: (1.3-1.5) mL: (0.1-0.15) g.
7. A high-strength flame-retardant nylon composition according to claim 5, characterized in that: The glass fiber has a diameter of 5-7 μm and a length of 2-3 mm.
8. A method for preparing a high-strength flame-retardant nylon composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: After the nylon resin, composite flame retardant and toughening agent are evenly mixed, they are added into a twin-screw extruder through a main feed port, and the modified glass fiber is added into the twin-screw extruder from a side feed port. After melt blending, extrusion granulation and drying, a high-strength flame-retardant nylon composition is obtained.
9. The method for preparing a high-strength flame-retardant nylon composition according to claim 8, characterized in that: The operating temperature of each zone of the twin-screw extruder is: 230-250° C. for zone 1, 240-270° C. for zone 2, 245-275° C. for zone 3, and 250-280° C. for zone 4; the screw speed of the twin-screw extruder is 330-450 rpm.
Citation Information
Patent Citations
Intumescent flame retardant for polyurethane, flame-retardant polyurethane and preparation of flame-retardant polyurethane
CN114672068A
Flame-retardant material
CN116218180A